Suicide from a Holistic Point of View - Søren Ventegodt; Joav Merrick (The Scientific World Journal)
Suicide has been honoured and respected in the eastern culture, especially in Japan with the famous tradition of Hara-kiri, or seppuku, while in most western societies suicide has been seen negatively and many contemporary physicians tend to consider suicide the most self-destructive and evil thing a human being can do and something that should be avoided at all cost. Religions also have different viewpoints on suicide, but from a philosophical point of view we believe that considering the choice of life and dead to be extremely relevant for a good living. The choice of life and dead is real, since responsibility for life is necessary in order to live life and even the best physician cannot keep a patient alive, who deep inside wants to die. In this chapter, we present parts of a story of a young girl who had experienced child sexual abuse. In holistic existential therapy, it is our experience, when the patient is well supported in the confrontation of the fundamental questions related to assuming responsibility for the coherence, that this confrontation will almost always lead to a big YES to life. Without confronting the fundamental question of “to be or not to be”, life can never be chosen 100% and thus never be lived fully.